Geographical, temporal and environmental determinants of bryophyte species richness in the Macaronesian Islands - Aranda, Silvia C. (2014)
Copyright: © 2014 Aranda et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.